Postirradiation Multiple Minute Digitate Porokeratosis: Case Report - Joana Lima; Marta Sousa; Pedro Andrade (Sociedade Portuguesa de Dermatologia e Venereologia, 2018)
Docetaxel is a second-generation taxane commonly used in the treatment of advanced malignant tumours such as breast adenocarcinoma. We describe the case of a 67-year-old female undergoing adjuvant chemotherapy with docetaxel for invasive ductal carcinoma of the left breast presenting with typical psoriatic lesions on the dorsum and limbs - the most representative of them arising close to the venous access for docetaxel infusion. No personal or family history of psoriasis was reported. The patient started and maintained treatment with oral acitretin and topical betamethasone diproprionate/calcipotriol for nearly eight months, with almost complete regression of cutaneous lesions. Drug-induced psoriasis is a rare condition. The most commonly reported drugs include beta-blockers, interferon and antimalarials. In this case we demonstrate that docetaxel should be included in the group of drugs that can potentially induce psoriasis.